2004
DOI: 10.1074/jbc.m409963200
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Studies on the Interaction of the Third Complement Component and Its Inhibitor, Compstatin

Abstract: Compstatin is a 13-residue cyclic peptide that inhibits complement activation by binding to complement component, C3. Although the activity of compstatin has been improved severalfold using combinatorial and rational design approaches, the molecular basis for its interaction with C3 is not yet fully understood. In the present study, isothermal titration calorimetry was employed to dissect the molecular forces that govern the interaction of compstatin with C3 using four different compstatin analogs. Our studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…High concentrations of C3 present in NHS make it difficult to deplete; therefore, we used compstatin to inhibit C3 activation and determine whether C3 is necessary to neutralize gC-null viruses. Compstatin (4W9A) is a small synthetic peptide that interferes with complement at low concentrations by binding C3, preventing its activation (29,30,45). Experiments were performed to examine neutralization following treatment with 20% NHS or 20% NHS treated with either active (4W9A) or (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of C3 present in NHS make it difficult to deplete; therefore, we used compstatin to inhibit C3 activation and determine whether C3 is necessary to neutralize gC-null viruses. Compstatin (4W9A) is a small synthetic peptide that interferes with complement at low concentrations by binding C3, preventing its activation (29,30,45). Experiments were performed to examine neutralization following treatment with 20% NHS or 20% NHS treated with either active (4W9A) or (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum to inactivate the classical and mannan-binding lectin pathways (20); and 100 mM D-mannose to interfere with activation of the mannan-binding lectin pathway (9,28). To interfere with C3 activation, NHS was treated with the small synthetic peptide compstatin (4W9A) at a concentration of 40 M, while 40 M linear compstatin was used as an inactive control (29,30,45).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Biophysical data confirmed a single binding site for compstatin on C3, while deviation from a simple kinetic 1:1 model in SPR indicated a conformational rearrangement of the peptide and/or protein upon binding (Katragadda et al 2004;Sahu et al 2000). Later, the binding region could be narrowed down to the C-terminal 40-kDa part of C3, which includes several macroglobulin domains (MG 3-6 β ) as well as the linker (LNK) C3b, and C3c (Janssen et al 2006;Wiesmann et al 2006) offered an unprecedented insight into the complement activation process.…”
Section: Exploring the Binding Site And Modementioning
confidence: 81%
“…Further thermodynamic analyses indicated that the C3-compstatin interaction is largely driven by enthalpic contributions. In this context, the beneficial effects of a valine-totryptophan substitution at position 4 (and also histidine-to-alanine at position 9) could be linked to an increased enthalpy and binding affinity to C3 (Katragadda et al 2004). …”
mentioning
confidence: 99%
“…Besides IC 50 activity measurements that were performed for each synthesized analog, kinetic and thermodynamic binding studies were performed using surface plasmon resonance [12,14], and isothermal titration calorimetry [15]. The structural, binding, and activity studies were useful to form testable structure-binding and structure-activity hypotheses.…”
Section: Results: the Example Of Compstatinmentioning
confidence: 99%